2021
DOI: 10.1002/aepp.13195
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural support and contaminated spillovers: The effects of agricultural water pollution on adult health in China

Abstract: Using rich longitudinal data combined with administrative water quality data from China, we examine the causal impact of agricultural water pollution on adult health outcomes. To obtain exogenous variation in agricultural water pollution, we use a quasi‐experimental design and exploit a series of agricultural support policies enacted in China in the mid‐2000s. We find that agricultural water pollution worsens health outcomes through increased incidence of morbidity and lower body mass index. We additionally fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Sewage with high levels of chloroacetic acid, nitrate, nitrite, heavy metals, and organic matter poses a risk to human health [4,22]. Therefore, traditional sewage purification methods need improvement to be more effective and cost-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Sewage with high levels of chloroacetic acid, nitrate, nitrite, heavy metals, and organic matter poses a risk to human health [4,22]. Therefore, traditional sewage purification methods need improvement to be more effective and cost-efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In rural China, while environmental degradation is of increasing concern to Chinese policy makers, environmental goals are often seen as secondary to those related to food production and economic growth. However, the health costs of environmental damage should not be overlooked in policy design targeting the improvement of rural livelihoods [16]. In short, environmental governance must strike a balance between environmental interests and economic interests: "While each right advances the interests of the rights holder, yet the reasons for protecting those interests, and those evidentiary reasons for protecting the right, are not limited to concerns for the well-being of the rights holder" [51].…”
Section: Balancing Economic and Environmental Interests In Rural Envi...mentioning
confidence: 99%
“…About 170,000 farmers die each year worldwide as a result of their occupational activities, and millions suffer from occupational health problems [15]. In China, overuse of fertilizers and pesticides and the toxic residues of pesticides left in water pose great health risks to families in rural areas [16]. Studies have found that exposure to pesticides has a wide range of long-term and short-term effects on the health of farmers.…”
mentioning
confidence: 99%
“…, biodiversity loss (Tsiafouli et al, 2015) and water pollution around the globe (Food and Agriculture Organization of the United Nations [FAO], 2017). According to the studies, agriculture is the leading culprit behind river and lake pollution in the United States (Evans et al, 2019), in China (FAO, 2013), where it is estimated to render a staggering 90% of shallow groundwater unfit for human consumption (Lu & Villa, 2022), and the EU (European Environmental Agency [EEA], 2018) severely affecting around 38% of EU water bodies. As expected, population growth, rising per capita food consumption (FAO, 2017) and changing climate is putting even more pressure on water ecosystems (Heathwaite, 2010).…”
mentioning
confidence: 99%